FACTORS INFLUENCING PERFORMANCE OF AGRICULTURAL COUNSELORS IN TOJO UNA-UNA REGENCY - Ahmad Firman; Mashur Razak (SEIKO : Journal of Management & Business, 2020)
This research was conducted to analyze factors which consist of work environment, incentives, non-financial rewards and placement that give impact on the performance of agricultural instructors in Tojo Una-Una Regency. Type of the current research is descriptive quantitative, 51 people of sample are agricultural counselor. Stratified Proportional Random sampling technique was applied and then processed by using SPSS application. The results showed that both partially and simultaneously work environment, incentives, non-financial rewards and placements had an effect on the performance of agricultural instructors in Tojo Una-Una Regency and the most dominant factor is incentives. Keywords: work environment, incentives, non-financial rewards, placement, performance of agricultural counselor